Integrasi Blockchain dan Artificial Intelligence dalam Transformasi Digital Maritime Supply Chain: Sebuah Tinjauan Sistematis terhadap Efisiensi dan Resiliensi - Karjono; Karmanis; Evyana Diah Kusumawati (JURNAL TRANSMA, 2026)
Background: The global maritime supply chain faces enormous pressure to undergo digital transformation amid demands for efficiency and resilience. Blockchain and Artificial Intelligence (AI) have emerged as key technologies, yet their integration has rarely been systematically reviewed. Objective: This study aims to synthesize scientific evidence on Blockchain-AI integration models, their contributions to maritime supply chain efficiency and resilience, and the factors influencing implementation.Method: A systematic literature review (SLR) following the PRISMA protocol was conducted. Searches were performed in Scopus, Web of Science, and Google Scholar (2019 2024) using structured keywords. A total of 128 articles from 152 initial references were thematically analyzed. Results: Three main integration patterns were identified: off-chain AI with on-chain smart contracts, on-chain federated learning, and hybrid oracle-based integration. Blockchain-AI integration has been proven to reduce turnaround time by 25 35%, document costs by 28 44%, and increase supply chain visibility by up to 92%. Resilience improved through disruption prediction (85 94% accuracy), automated rerouting, and reduction of recovery time by up to 57%. The main barriers are interoperability, regulation, and migration costs. Simultaneous Blockchain-AI integration enhances both efficiency and resilience of maritime supply chains, but requires interoperability standards and regulatory support.